Test-retest reliability of a pendant-worn sensor device in measuring chair rise performance in older persons - Zhang, Wei; Regterschot, G Ruben H; Schaabova, Hana; Baldus, Heribert; Zijlstra, Wiebren (Sensors, 2014)
Chair rise performance is incorporated in clinical assessments to indicate fall risk status in older persons. This study investigated the test-retest reliability of a pendant-sensor-based assessment of chair rise performance. Forty-one older persons (28 females, 13 males, age: 72-94) were assessed in two sessions with 3 to 8 days in between. Repeated chair rise transfers were measured after different instructions. Relative and absolute test-retest reliability of chair rise measurements in individual tests and average over all tests were evaluated by means of intra-class correlation coefficients (ICCs) and standard error of measurement (SEM) as a percentage of the measurement mean. Systematic bias between the measurements in test and retest was examined with paired t-tests. Heteroscedasticity of the measurements was visually checked with Bland-Altman plots. In the different test conditions, the ICCs ranged between 0.63 and 0.93, and the SEM% ranged between 5.7% and 21.2%. The relative and absolute reliability of the average over all tests were ICC = 0.86 and SEM% = 9.5% for transfer duration, ICC = 0.93 and SEM% = 9.2% for maximum vertical acceleration, and ICC = 0.89 and SEM% = 10.0% for peak power. The results over all tests indicated that a fall risk assessment application based on pendant-worn-sensor measured chair rise performance in daily life might be feasible.
Keywords: Accelerometry; aktigrafie; Equipment Design; Movement; Female; analýza selhání vybavení; akcelerometrie; pohyb; Geriatric Assessment; ženské pohlaví; Reproducibility of Results; Monitoring, Ambulatory; lidé; postura těla; Sensitivity and Specificity; Postural Balance; geriatrické hodnocení; Aged, 80 and over; senzitivita a specificita; Equipment Failure Analysis; Actigraphy; reprodukovatelnost výsledků; Male; Aged; Posture; ambulantní monitorování; senioři nad 80 let; senioři; mužské pohlaví; design vybavení; posturální rovnováha; Humans